Cobalt nanocrystals embedded into N-doped carbon as highly active bifunctional electrocatalysts from pyrolysis of triazolebenzoate complex. (10th September 2018) - Wei, Zhaojun; Yang, Yang; Liu, Minmin; Dong, Jing; Fan, Xiujun; Zhang, XianMing
Abstract: A new and highly-efficient electrocatalyst, constructed by surface enwraped Co nanocrystyals (NCs) embedded into 2-dimensional N -doping graphitized carbon layer (Co@NC), is synthesized by simple one-pot thermal treatment of complex Co(tzbc)2 (H2 O)4 (tzbc = 4-(1H-1, 2, 4-triazol-1-yl) benzoate). The utilization of stoichiometrically clear Co(tzbc)2 (H2 O)4 as precursor could reap following benefits: i) sp 2 carbon and nitrogen in tzbc groups could directly convert to N -doping graphitized carbon; ii) metallic Co NCs formed from the thermal reduction of Co 2+ in Co(tzbc)2 (H2 O)4, which can subsequently catalyze the graphitization of the obtained carbons, avoiding additional reducing agent or using potentially dangerous atmosphere; iii) most importantly, complex precursor is easily available and could synthesize in a large scale by simple stirring reaction. As a result, the Co@NC catalyst exhibits excellent activity and stability toward both hydrogen and oxygen evolution reactions (HER and OER, respectively), approaching electrocatalytic performance shown by state-of-the-art Pt and RuO2 . Such excellent HER and OER activities are attributed to the synergistic effect of the surface enwraped cobalt nanocrystyals and high conductivity of N -doped graphitized carbon. Graphical abstract: Image 1